Comparison of the effects of different retention appliances on the oxidant–antioxidant system. Issue 15 (2nd August 2016) - Goymen, Merve; Sokucu, Oral; Taysi, Seyithan; Topcuoglu, Tolga; Tarakcioglu, Mehmet
Abstract: The aim was to compare oxidative stress (OS) levels with different types of retention appliance. Thirty orthodontic patients were divided into three groups: Group 1 (Essix retainer), Group 2 (lingual retainer with stainless steel retainer wire), and Group 3 (lingual retainer with fiber-reinforced material). OS was assessed in the subjects' saliva. Saliva samples were taken from the patients at T 0 (before using the retention appliance), T 1 (first month of retention), and T 2 (third month of retention). The specimens were investigated to detect changes in total antioxidant status (TAS), total oxidant status (TOS), and oxidative stress index (OSI). TAS values in Group 2 were significantly higher than in Group 3. TOS values in Group 3 were significantly lower than in the other groups. TOS values in Group 2 were lower than in Group 1. OSI values of Group 1 were higher than those in Group 2 or 3. There was no statistically significant difference among the time periods. The type of retention appliance affected OS values. A fiber-reinforced material may have a lower OSI. OS or products can affect some systemic disease; therefore, the selection of the retainer will be important on these patients.